RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION TO THE EVENTS OF DIARRHEA IN BEHAVIOR IN THE WORKING AREA OF PUSKESMAS WAEL DISTRICT WEST SERAM 2017. - Sunik Cahyawati (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Diarhea remains the second rank as leading cause prevantable dearth in chidren. Earch year about 2,5 billion cases of diarrhea in childer under five years. Diarrhea remains leading cause o perentable in children as a group have higher incident. The aim o this study to know relationship between environment sanitation to diarrhea in hidren under five yares at area of community hearlt center Wael West o seram 2017. The study used croos sectiona study with 40 responden (total sampling). Data has analyzed with chi-square test. The result showt that there was significant relationship between source of water (p=0,002), having water of closet (p=0,001) , and kind of floor (p=0,002) thMeode. The method used is cross-sectional by interviewing 40 mothers who have sample toddlers who did total data sampling using the chi-square test. Keywords: diarrhea, drinking water sources, ownership of latrines, and the floor of the house.